"Bring Out Your Dead": Understanding the Historical Persistence of the Criminalization of Black Bodies. (June 2016) - Bey, Marquis
This essay speaks to the criminalization of Black bodies via the purported "confession" of wrongdoing that Blackness makes through the interpretive White gaze. Blackness operates as a site of always imminently actualized criminality or pathology that must be quelled or eradicated. Using James Baldwin's meditation on the function of Wayne Williams's body as a historical anchor, this essay seks to articulate the contemporary ways in which Black bodies are positioned via the White gaze, as well as demonstrate the continuity of anti-Black violence, itself predicated on what Charles Mills calls an "epistemology of ignorance."